1997
DOI: 10.1042/cs0930127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Training on Metabolic Control in Elderly Type 2 Diabetes Mellitus Patients

Abstract: 1. The specific role of physical activity in the treatment of type 2 diabetes is still subject to discussion. A randomized prospective study was performed, investigating both the influence of physical training on metabolic control and the feasibility of physical training in the elderly. 2. A total of 58 patients (mean age: 62 +/- 5 years; range: 55-75 years) with type 2 diabetes were randomized to either a physical training or a control programme. The training programme consisted of three sessions a week, aimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2
16

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 17 publications
4
64
2
16
Order By: Relevance
“…The present study adds significantly to the literature on the health benefits of exercise for type 2 diabetes mellitus patients. Ligtenberg [27] examined the effects of supervised aerobic exercise training in 51 type 2 diabetic patients and found improvements in aerobic capacity and blood lipid variables that favoured the exercise training group compared with a control group; there were no improvements in glycaemic control or insulin sensitivity. In a subsequent analysis [28], they found improvements in anxiety, energy and positive well-being, but not depression (measured by the 22-item version of the WBQ) favouring the aerobic exercise training group.…”
Section: Discussionmentioning
confidence: 99%
“…The present study adds significantly to the literature on the health benefits of exercise for type 2 diabetes mellitus patients. Ligtenberg [27] examined the effects of supervised aerobic exercise training in 51 type 2 diabetic patients and found improvements in aerobic capacity and blood lipid variables that favoured the exercise training group compared with a control group; there were no improvements in glycaemic control or insulin sensitivity. In a subsequent analysis [28], they found improvements in anxiety, energy and positive well-being, but not depression (measured by the 22-item version of the WBQ) favouring the aerobic exercise training group.…”
Section: Discussionmentioning
confidence: 99%
“…The few intervention studies undertaken in older diabetic adults have reported conflicting results. Ligtenberg et al (1997) found no significant differences in HbA 1c between training and control groups after 12 weeks of physical training, while Raz et al (1994) observed a significant reduction in slightly younger patients following a similar programme of the same duration. In our study, no participants were classified as having high overall physical activity and very few were walking long or frequently enough to favourably influence HbA 1c (Yeater The effect of overall activity on BMI was found to be different for male and female subjects (interaction effect); therefore, ratios of the geometric mean of BMI for medium versus low activity are displayed separately for male and female subjects.…”
Section: Multivariate Model Developed For Hba 1cmentioning
confidence: 92%
“…Most metabolic studies find a significant effect of exercise on glucose control [22][23][24] and on triglycerides. 25,26 A meta-analysis of clinical trials on the effect of exercise on glucose control found that interventions longer than 8 weeks reduced HbA1c from 8.31% to 7.65% (weighted mean difference 0.66%, PϽ0.001) independently of body mass. This effect is clinically important and is likely to reduce diabetic complications in a significant manner.…”
Section: Discussionmentioning
confidence: 99%